Photoredox-catalyzed silyldifluoromethylation of silyl enol ethers - Supranovich, Vyacheslav I.; Levin, Vitalij V.; Dilman, Alexander D. (Beilstein Journal of Organic Chemistry, 2020)
A method for the light-mediated fluoroalkylation of silyl enol ethers with (bromodifluoromethyl)trimethylsilane followed by a reduction of the primary products with sodium borohydride is described. An 18 W, 375 nm LED was used as the light source. The reaction is performed in the presence of a gold photocatalyst, which effects the generation of a (trimethylsilyl)difluoromethyl radical via cleavage of the carbon–bromine bond.
Keywords: difluoroalkylation; organofluorine compounds; photocatalysis; radical addition; silicon reagents

(untitled) - Prakash, G. K. S.; Yudin, A. K. (Chem. Rev., 1997)

(untitled) - Liu, X.; Xu, C.; Wang, M.; Liu, Q. (Chem. Rev., 2015)

(untitled) - Krishnamoorthy, S.; Prakash, G. K. S. (Synthesis, 2017)

(untitled) - Uneyama, K. (J. Fluorine Chem., 2008)

(untitled) - Dilman, A. D.; Levin, V. V. (Mendeleev Commun., 2015)

(untitled) - Yan, M.; Lo, J. C.; Edwards, J. T.; Baran, P. S. (J. Am. Chem. Soc., 2016)

(untitled) - Zard, S. Z. (Org. Lett., 2017)

(untitled) - Studer, A. (Angew. Chem., Int. Ed., 2012)

(untitled) - Barata-Vallejo, S.; Cooke, M. V.; Postigo, A. (ACS Catal., 2018)

(untitled) - Koike, T.; Akita, M. (Acc. Chem. Res., 2016)

(untitled) - Koike, T.; Akita, M. (Org. Biomol. Chem., 2019)

(untitled) - Lemos, A.; Lemaire, C.; Luxen, A. (Adv. Synth. Catal., 2019)

Modern Synthesis Processes and Reactivity of Fluorinated Compounds - Dagousset, G.; Carboni, A.; Masson, G.; Magnier, E. (Visible Light–Induced (Per)fluoroalkylation by Photoredox Catalysis, 2017)

(untitled) - Kosobokov, M. D.; Dilman, A. D.; Levin, V. V.; Struchkova, M. I. (J. Org. Chem., 2012)

(untitled) - Li, L.; Wang, F.; Ni, C.; Hu, J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Xie, Q.; Ni, C.; Zhang, R.; Li, L.; Rong, J.; Hu, J. (Angew. Chem., Int. Ed., 2017)

(untitled) - Xie, Q.; Zhu, Z.; Li, L.; Ni, C.; Hu, J. (Angew. Chem., Int. Ed., 2019)

(untitled) - Dilman, A. D.; Levin, V. V. (Acc. Chem. Res., 2018)

(untitled) - Kosobokov, M. D.; Levin, V. V.; Struchkova, M. I.; Dilman, A. D. (Org. Lett., 2015)

(untitled) - Fedorov, O. V.; Kosobokov, M. D.; Levin, V. V.; Struchkova, M. I.; Dilman, A. D. (J. Org. Chem., 2015)

(untitled) - Supranovich, V. I.; Levin, V. V.; Struchkova, M. I.; Korlyukov, A. A.; Dilman, A. D. (Org. Lett., 2017)

(untitled) - Pham, P. V.; Nagib, D. A.; MacMillan, D. W. C. (Angew. Chem., Int. Ed., 2011)

(untitled) - Panferova, L. I.; Tsymbal, A. V.; Levin, V. V.; Struchkova, M. I.; Dilman, A. D. (Org. Lett., 2016)

(untitled) - Chernov, G. N.; Levin, V. V.; Kokorekin, V. A.; Struchkova, M. I.; Dilman, A. D. (Adv. Synth. Catal., 2017)

(untitled) - Zidan, M.; Rohe, S.; McCallum, T.; Barriault, L. (Catal. Sci. Technol., 2018)

(untitled) - Revol, G.; McCallum, T.; Morin, M.; Gagosz, F.; Barriault, L. (Angew. Chem., Int. Ed., 2013)

(untitled) - Li, D.; Che, C.-M.; Kwong, H.-L.; Yam, V. W.-W. (J. Chem. Soc., Dalton Trans., 1992)

(untitled) - Prier, C. K.; Rankic, D. A.; MacMillan, D. W. C. (Chem. Rev., 2013)

(untitled) - Shaw, M. H.; Twilton, J.; MacMillan, D. W. C. (J. Org. Chem., 2016)

(untitled) - Tsymbal, A. V.; Kosobokov, M. D.; Levin, V. V.; Struchkova, M. I.; Dilman, A. D. (J. Org. Chem., 2014)